Multi-Criteria Decision Making for Sustainable Materials of Textile SMEs in Indonesia - Sayyidah Maulidatul Afraah; Dwi Adi Purnama; Arif Hidayat; Diyah Dwi Nugraheni (Universitas Sultan Ageng Tirtayasa, 2026)
The increasing global emphasis on sustainability has pushed the traditional textile industry, including batik SMEs (Small and Medium Enterprises), to adopt environmentally responsible practices, particularly in the selection of raw materials. This study aims to identify and analyze the key criteria for selecting sustainable raw materials, both fabric and dye in the batik industry and to determine the best alternatives using the Multi-Criteria Decision Making, especially Analytic Hierarchy Process (AHP) method. This research established five main criteria: environmental impact, economic aspects, social factors, product quality, and production-technology compatibility. This research also established 14 sub-criteria based on main criteria. This reseach collected data from experts and batik SME owners through pairwise comparison questionnaires and analyzed using AHP. The results indicate that product quality holds the highest priority, and economic and environmental aspects as the second priority. Based on fabric options, the most preferred material is tencel/lyocell, due to its superior comfort, dye absorption, and eco-friendly production process. Based on dyes options, the most suitable alternative is recycled plant-based extracts, offering both environmental benefits and good color performance. The combination of Tencel/Lyocell and recycled plant-based dye presents a sustainable raw material strategy that supports environmentally responsible batik production and enhances the competitive value of SMEs in the textile sector.